Association between gamma-glutamyl transferase and risk of major adverse cardiovascular events in patients with hypertrophic cardiomyopathy: a retrospective cohort study - Meng Yao; Xiaoyin Xing; Zhe Chen; Cunying Cui; Xinqiao Tian (Frontiers in Cardiovascular Medicine, 2026)
Background Hypertrophic cardiomyopathy (HCM) is the most common hereditary heart disease, and the subsequent major adverse cardiovascular events (MACE) pose a serious threat to the health of patients. This investigation was intended to explore the association between gamma-glutamyl transferase (GGT) levels and MACE risk in patients with HCM. Methods Data from patients (≥ 18 years old) diagnosed with HCM at a hospital were enrolled in this retrospective cohort study. The association between GGT levels and the risk of MACE was assessed using Cox regression models. Subgroup analyses were conducted according to HCM subtypes (non-obstructive, resting obstructive, latent obstructive) and New York Heart Association (NYHA) grades (I/II, III/IV). Results The analysis cohort consisted of 437 patients with HCM, of whom 163 (37.30%) patients experienced MACE, while 274 (62.70%) remained MACE-free. GGT levels of 20–57 U/L [HR = 1.72 (95%CI: 1.13–2.62)] and ≥57 U/L [HR = 2.29 (95%CI: 1.30–4.03)] were both associated with a higher risk of MACE than those with GGT <20 U/L. Subgroup analysis found that GGT levels of 20–57 U/L [HR = 2.25 (95%CI: 1.15–4.37)] and ≥57 U/L [HR = 3.66 (95%CI: 1.44–9.28)] were both linked to an increased risk of MACE in those with non-obstructive HCM, whereas no significant association was detected in those with resting obstructive HCM and latent obstructive HCM. Moreover, GGT levels of 20–57 U/L [HR = 1.78 (95%CI: 1.07–2.97)] and ≥57 U/L [HR = 2.97 (95%CI: 1.51–5.83)] were both linked to an elevated risk of MACE in patients with NYHA grade I/II. Conclusion Elevated GGT levels were associated with a higher risk of MACE among patients with HCM. GGT may serve as a clinical red flag for MACE risk.